Customer Experience of Electronic Services in Information Technology Organizations Based on Digital Developments - Fatemeh Saeedi; Abolfazl Danaei; Seyed Mohammad Barzegar (International Journal of Digital Content Management, 2022)
Purpose: Customer experience management is one of the most important activities for managers who are trying to grow and develop to achieve a favorable competitive position. The purpose of this study is to evaluate the dimensions of customer experience in the process of using electronic services in information technology organizations (Hamrah-e-Aval).Method: The method of this study is quantitative. In this regard, a questionnaire was designed and distributed among the statistical population by the available sampling method. The data analysis method is structural equation modeling and the software used is SPSS25 and SMART PLS 3.0.Findings: Findings show that awareness is the first step in managing customer experience. The second step deals with the active organizational actor. The third step, or evaluation, is based on service characteristics and service arrangements. The fourth step (buying decision). Purchasing and the resulting experience is the fifth step. Step 6 (Use) is a function of activities including delivery and use. The seventh step is to repeat the purchase, complain or not react to the use of the product (service). Finally, the customer's secondary response is the last step of the customer experience model.Conclusion: Based on the findings of the present study, information interface can play a decisive role in shaping customer experiences. Therefore, it is suggested that in the active businesses in the information and communication technology industry, by studying the media and customer information tools, the most optimal and effective tools should be selected and used.